2021
DOI: 10.1111/ans.16853
|View full text |Cite
|
Sign up to set email alerts
|

Australian experience with total pancreatectomy with islet autotransplantation to treat chronic pancreatitis

Abstract: Background: This study aimed to describe the clinical outcomes of total pancreatectomy with islet autotransplantation (TP-IAT) in Australia. Methods: Individuals selected for TP-IAT surgery according to the Minnesota Criteria (Appendix) without evidence of diabetes were evaluated including time to transplantation from pancreatectomy, islet numbers infused and post-transplantation HbA1c, C-peptide, total daily insulin and analgesic requirement. Results: Sixteen individuals underwent TP-IAT from Australia and Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Further, 12% of adults admitted to hospital because of chronic pancreatitis were Indigenous people, some of whom may have had undiagnosed hereditary pancreatitis. A 2004 case report 25 described an Indigenous family with several members who had hereditary pancreatitis; in our reports on total pancreatectomy and islet auto‐transplantation (TP‐IAT), most patients with hereditary pancreatitis were also Indigenous people 5,16 . The prevalence of exocrine pancreas disorders is generally higher in indigenous than European origin populations 24 .…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Further, 12% of adults admitted to hospital because of chronic pancreatitis were Indigenous people, some of whom may have had undiagnosed hereditary pancreatitis. A 2004 case report 25 described an Indigenous family with several members who had hereditary pancreatitis; in our reports on total pancreatectomy and islet auto‐transplantation (TP‐IAT), most patients with hereditary pancreatitis were also Indigenous people 5,16 . The prevalence of exocrine pancreas disorders is generally higher in indigenous than European origin populations 24 .…”
Section: Discussionmentioning
confidence: 89%
“…Diabetes secondary to chronic pancreatic inflammation might be averted by TP‐IAT, a new treatment in which the pancreas is removed, and its islet cells are isolated and infused into the liver. Our experience with this procedure is that, if undertaken early, it can greatly improve the quality of life of people with hereditary pancreatitis in terms of pain relief and prevention of type 3c diabetes 5,6,16 . Twenty‐nine people in our study (66%) fulfilled the Minnesota criteria for the appropriateness of TP‐IAT for patients with chronic pancreatitis, taking history of recurrent acute pancreatitis, medical imaging and biochemistry findings, lifestyle, and need for narcotic medications into account 5,6,16 …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…28 Table 2 and Figure 2 show the demographic characteristics of studies on TPIAT for CP and RAP at institutions in the United States, United Kingdom, and Australia. 22,[29][30][31][32][33] The optimal timing of TPIAT is a sensitive issue. In recent years, previous studies have reported the superiority of early surgical intervention to nonsurgical treatment for CP.…”
Section: Ind Ic Ati On and Timing Of Tpiatmentioning
confidence: 99%